2011
DOI: 10.1080/02508060.2011.594868
|View full text |Cite
|
Sign up to set email alerts
|

Evolving policies and the roles of public and private stakeholders in wastewater and faecal-sludge management in India, China and Ghana

Abstract: In this article the authors document evolving attitudes, policies and roles of stakeholders in wastewater and faecal-sludge management in India, China and Ghana. In each country there is momentum for expanding not just access to sanitation at the household/community levels, but also for greater treatment and safe end-of-life management of human excreta. Governments are increasingly looking to engage the private sector, but models of engagement that make a compelling business case and instil confidence in cost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…In most countries in SSA, FS collected from on-site sanitation technologies is discharged untreated onto surrounding land, watercourses or used untreated in agriculture or aquaculture (Klingel et al, 2002), contributing to health hazards and water pollution. For example, Murray et al (2011b) reported that only a small fraction (10%) of the collected FS in all major cities of Ghana as being treated. The rest is directly discharged in the ocean.…”
Section: Disposal and End-use Of Faecal Sludge In Ssamentioning
confidence: 99%
“…In most countries in SSA, FS collected from on-site sanitation technologies is discharged untreated onto surrounding land, watercourses or used untreated in agriculture or aquaculture (Klingel et al, 2002), contributing to health hazards and water pollution. For example, Murray et al (2011b) reported that only a small fraction (10%) of the collected FS in all major cities of Ghana as being treated. The rest is directly discharged in the ocean.…”
Section: Disposal and End-use Of Faecal Sludge In Ssamentioning
confidence: 99%
“…By contrast, during the 1980s the West Bengal government in India established development control measures to ensure the preservation of the 125 km 2 East Kolkata wetland that both treats urban wastewater and hosts peri-urban fisheries crops and rice paddies (Ghosh 1999;2014). Health issues related to use of wastewater in agriculture and aquaculture practices are a concern and need to be managed, but globally there is a long history of wastewater reuse and studies indicate there are economic and environmental benefits when practised appropriately (Drechsel and Seidu 2011;Heinz et al 2011;Jimenez and Asano 2008;Miller 2006;Murray et al 2011;Weldesilassie et al 2011;Wichelns et al 2011 ). Health risks related to use of Boeng Cheung Ek have been examined elsewhere (Chea et al 2010;Marcussen et al 2009;Ngoen-Klan et al 2010) and currently the primary risk seems to be from biological (rather than chemical) vectors, which can be more easily managed through public education.…”
Section: The Way Forward-urban Planning and The Wetlands Of Phnom Penhmentioning
confidence: 99%
“…It is even noted that pit latrine emptying services are needed to keep a sanitation ladder functioning. Murray et al (2010) also notes in a review of national policy for India, China and Ghana, overly ambitious targets of 100% compliance may not be reasonable. Moving forward, the model chosen by Ghana to stair step sanitation legislation between 2008 and 2024 may be an ideal model of momentum for both Malawi and Zambia to follow rather than the model in India where a 2002 National Water Policy with 100% urban wastewater treatment target has major gaps in enforcement (Murray et al, 2010).…”
Section: What Needs To Change To Overcome the Key Challenges?mentioning
confidence: 99%
“…Murray et al (2010) also notes in a review of national policy for India, China and Ghana, overly ambitious targets of 100% compliance may not be reasonable. Moving forward, the model chosen by Ghana to stair step sanitation legislation between 2008 and 2024 may be an ideal model of momentum for both Malawi and Zambia to follow rather than the model in India where a 2002 National Water Policy with 100% urban wastewater treatment target has major gaps in enforcement (Murray et al, 2010). Furthering this Linyama et al (2014) reports on a Lusaka monitoring process under WSUP for pit latrine emptiers, including a job card, customer data sheet, field log book and global monitoring sheet.…”
Section: What Needs To Change To Overcome the Key Challenges?mentioning
confidence: 99%